Clinical Pharmacist-Led Medication Review in Hospitalized Confirmed or Probable Patients with COVID-19 During the First Wave of COVID-19 Pandemic - ÜNDER, DUYGU; ENVER, CÜNEYD; DEMİRCİ, MUHAMMED YASİR; AYHAN, YUNUS EMRE; ÖZGAN, BETÜL; İLERLER, ENES EMİR; OKUYAN, BETÜL; ERTÜRK ŞENGEL, BUKET; KOCAKAYA, DERYA; SİLİ, ULUHAN; TİGEN, ELİF; KARAKURT, SAİT; et al. (My University, 2024)
Objectives: Drug-related problems (DRPs) result in serious problems among hospitalized patients, high rates of morbidity and mortality, and increased healthcare costs. This study aimed to identify DRPs by clinical pharmacist-led medication review in hospitalized probable patients with coronavirus disease-2019 (COVID-19) during the first wave of the COVID-19 pandemic. Materials and Methods: This retrospective cross-sectional study was conducted at the COVID-19 inpatient services of a tertiary university hospital in Türkiye for 3 months (between March 2020 and June 2020) and included hospitalized confirmed or probable COVID-19 patients. The World Health Organization and Turkish Ministry of Health Guidelines case definitions were used to define confirmed and probable COVID-19 patients. Six clinical pharmacy residents provided medication review services during their education and training. DRPs were classified based on the Pharmaceutical Care Network Europe V9.00. The physician’s acceptance rate of clinical pharmacists’ recommendations was assessed. Results: Among 202 hospitalized patients with probable or confirmed COVID-19, 132 (65.3%) had at least one drug-related problem. Two hundred and sixty-four DRPs were identified. Drug selection (85.6%) and dose selection (9.2%) were the most common causes of these problems. Among the 80 clinical pharmacist interventions, 48.8% were accepted by the physicians. Conclusion: Clinical pharmacists identified a significant number of DRPs during the COVID-19 pandemic, particularly those related to drug interactions and drug safety, such as adverse drug reactions. This study highlights the importance of detecting and responding to DRPs in the COVID-19 pandemic.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TROPİKAL TIP; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MICROBIOLOGY; TROPICAL MEDICINE; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Moleküler Tıp; Farmasötik bilim; Molecular Medicine; Pharmaceutical Science; clinical pharmacist; COVID-19; drug-related problem; medication review; PCNE